Acute Respiratory Distress Syndrome in Patients with Cardiovascular Disease - Asma Zainab; Megan Gooch; Divina M. Tuazon (Methodist DeBakey Cardiovascular Journal)
Heart and lung interaction within the thoracic cavity is well known during inhalation and exhalation, both spontaneously and during mechanical ventilation. Disease and dysfunction of one organ affect the function of the other. A review of the cause-and-effect relationship between cardiovascular disease and acute respiratory distress syndrome (ARDS) is of significance, as the disease burden of both conditions has both a national and global impact on health care. This literature review examines the relationship between cardiovascular disease and ARDS over the past 25 years.